2002
DOI: 10.1037/0278-6133.21.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Testing mediating variables in a school-based nutrition intervention program.

Abstract: This study identified mediators of a school-based nutrition intervention for 4th graders and their parents. Nine variables were tested for satisfying 4 conclusions necessary to establish mediation of intervention effects on changes in fruit and vegetable consumption (FVC) in 4th graders (N = 1,676). FVC was measured in children by the use of 24-hr dietary recalls. Mediators were assessed by the use of questionnaires completed by children and parents. All 4 conclusions were met for positive outcome expectancies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
93
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(98 citation statements)
references
References 39 publications
4
93
1
Order By: Relevance
“…Also important is studying whether these correlates mediate changes in intake. Such mediation studies are clearly lacking 5,32 .…”
Section: Discussionmentioning
confidence: 99%
“…Also important is studying whether these correlates mediate changes in intake. Such mediation studies are clearly lacking 5,32 .…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of mediators focuses on the effect that an intervention program has on intervening variables and then subsequently examines the link between intervening variables and outcome measures (Baron and Kenny, 1986). This can provide a check on whether interventions changed the targeted intervening variables, extend an understanding of the success or failure of intervention materials, and help to test theories underlying prevention programs (Hansen and McNeal, 1997;Krull and MacKinnon, 1999;MacKinnon 1994;MacKinnon et al 1991;Reynolds et al, 2002). While much information can be gained from mediational analysis, this technique clearly remains underutilized (Baron and Kenny, 1986;MacKinnon et al, 1988;Reynolds et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Adolescents utilize proxy agency when they believe that others, such as parents and school staff, can assist them. Although proxy agency is reflected in self-efficacy assessments, studies of correlates of PA and FV have shown some promise in identifying the proxy agency process of behavior change by developing proxy efficacy scales (Dzewaltowski et al, 2007) and by examining correlates of health behavior with proxy efficacy items in self-efficacy measures (e.g., Reynolds, Yaroch, Franklin, & Maloy, 2002), environmental change efficacy measures (Ryan & Dzewaltowski, 2002), and support-seeking measures (Saunders et al, 1997).…”
mentioning
confidence: 99%